Implementasi Kebijakan Penyelenggaraan Pendidikan Inklusi di SMP Negeri 27 Medan - Muhammad Iqbal; Siti Nur Aisah Solin; Hafiza Tasya Harahap; Hasmar Sulaiman (Journal on Education, 2023)
Inclusive education is to provide education system that provides opportunities for all learners with special needs to be able to follow education or learning in an educational setting together with the learners in general (East Java Governor Regulation, No. 6 of 2011). In the implementation of policy implementation implementation of inclusive education in six schools Organising Inclusive Level Elementary School and Junior High School, was found several classical problems, namely a lack of teachers Educators Lodging, unavailability of dedicated space for the handling of Children with Special Needs, no psychologists or guidance counseling, lack of socialization on inclusive education in the community around the school, and lack of knowledge about of Children with Special Needs regular teachers. The purpose of this study was to describe the implementation of the Government policy of inclusive education at the level of elementary and junior high school levels. This type of research is descriptive research with a qualitative approach. The focus of research on the implementation or operation of the implementation of inclusive education by using the theory Merile S. Grindle, while the data collection used observation, interview, documentation and triangulation.